Financial Intermediation and Monetary Policy Effectiveness in Nigeria - Okoro, Okoro E.U.; Manasseh, Charles O.; Abada, Felicia C.; Nzidee, Williams A.; Okeke, Ambrose C.; Onwumere, Josaphat U.J. (International Review of Management and Marketing, 2018)
The need to be able to assess properly the extent of the relationship between financial intermediation and monetary policies of the Central Bank of Nigeria (CBN) gave rise to the study on ‘impact of Financial Intermediation on Monetary Policy Effectiveness in Nigeria'. It is evidently clear that financial systems world over are heavily regulated in order to achieve the macroeconomic objectives of the government. Nigeria is not an exception. For this reason, the study estimated the impact of interest rate on bank loans and advances. The study further investigates the impact of cash reserve ratio on demand deposit. The data for study were sourced from CBN statistical bulletin which was estimated using ordinary least square method. The results showed that interest rate have significant impact on bank loan and advances, while cash reserve ratio has positive and significant impact on demand deposit. Consequently, the study recommended that the Central Bank (CBN) and the authorities of the Nigeria Financial system should ensure that the effectiveness of monetary policies is maintained at all times. Also, effort should be made by the apex bank to promote the activities of the commercial banks in intermediary role and should be integrated as a primary role of the commercial banks in Nigeria. Keywords: Financial Intermediation, Monetary Policy effectiveness, Cash Reserve Ratio JEL Classifications: E52, G2 DOI: https://doi.org/10.32479/irmm.7273